The Role of Parents in Shaping Children's Character during Online Learning during the Pandemic Period at MI Muhammadiyah Butuh 2 - Lailatul Mufida; Imron Imron (Prosiding University Research Colloquium, 2021)
This study aims to find out how big the role of parents in shaping the character orpersonality of children when they study at home during this pandemic. The pandemic thathas occurred in Indonesia has been going on for more than a year. This is certainly achallenge for parents who have children at school age. Children will interact more oftenwith their families when they ask their parents for help when doing their schoolwork.When they interact, namely between parents and children, parents must be ready to facechallenges. The challenge is how they instill the morals of children towards their parents,when they interact in learning because usually children will underestimate their parentsmore than their teachers when they study. Most parents think that learning with theirparents is certainly more difficult than with the teacher, of course, in terms of characterbuilding. If with the teacher the child will tend to be more obedient, more respectful, moreappreciative, etc. The research method chosen is a qualitative method. Data collectiontechniques used in the form of observations and interviews with a number of parents whohave children at school age. The results of the study show that the attitude of childrenwhen they study with their parents is very concerning. There are still many who oftenshow disrespectful attitudes when studying with their parents. This is acknowledged bysome parents who sometimes often fight with their children when they study at home.Based on the results of the study, it can be concluded that the influence of parents ininstilling children's character during a pandemic is very large. As a parent, you should bemore assertive when the child has done things that are not in accordance with hischaracter. In this case the cultivation of children's character should also be monitored andsupervised by the teacher.